Decoding Users’ Continuance Intentions towards Digital Financial Platforms in the Indian Economy - Elangovan, Anandhi; Babu, Manivannan (International Review of Management and Marketing, 2024)
Indian financial sector has seen a dramatic change in recent years, with digital finance unlocking new possibilities for financial inclusion. This paper investigates the factors influencing the continuous usage intention and advocacy intention, regarding digital finance, in the Indian economy. Utilizing the Stimulus-Organism-Response (S-O-R) model, the study examines how ease of use, credibility and ubiquity (stimulus) could influence user trust, satisfaction, and engagement (organism), ultimately affecting their intention to use and recommend the service (response) continuously. Non-probability convenience sampling technique was used to select the study sample. Based on the results, features of digital financial platforms such as ease of use, credibility and ubiquity, were found to have a significant impact on user trust, satisfaction, and engagement. These factors partially mediate the stimulus and response variables. The research findings provide Digital Financial Service Providers (DFSPs) with practical guidance on creating and implementing user-centric platforms that create engagement and trust. User experience should be prioritized and making sure that platform should be accessible, easy to use and compatible with a variety of devices.